Implementasi Steganografi Dengan Metode Algoritma Least Significant Bit Untuk Menyisipkan Pesan Teks Pada Gambar - Sitorus, Lamria; William Panjaitan; Inggrid Pardede (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2026)
Steganography is an art in hiding data information in a media that is not suspicious where only the intended person knows the information. One of the popular steganography techniques is the Least Significant Bit (LSB) which is often used to hide confidential information into digital files such as images, audio, and even video. This research will produce an implementation of steganography with the LSB method to insert text into images that will provide protection for secret messages without reducing or damaging the visual quality of the image. This technique will take the least important bit which will then be given a text message insertion. In the process of inserting messages with this method, binary message data will be inserted into the bits on each color component (Red, Green, Blue) in the image pixels sequentially. Then the extraction process will be carried out in retrieving the message that was previously inserted into the digital image. Based on the implementation results, it shows that the LSB method has a high success rate in inserting text messages without any difference between the original image and the steganography results. Then the text can also be extracted as long as there has been no modification process on the image. The results of this implementation will further provide an overview that steganography techniques can be the best solution for simple but efficient data protection.